2013
DOI: 10.1103/physrevlett.111.127002
|View full text |Cite
|
Sign up to set email alerts
|

Imaging the Three-Dimensional Fermi-Surface Pairing near the Hidden-Order Transition inURu2Si2Using Angle-Resolved Photoemission Spectroscopy

Abstract: We report angle-resolved photoemission spectroscopy experiments probing deep into the hidden-order state of URu(2)Si(2), utilizing tunable photon energies with sufficient energy and momentum resolution to detect the near Fermi-surface (FS) behavior. Our results reveal (i) the full itinerancy of the 5f electrons, (ii) the crucial three-dimensional k-space nature of the FS and its critical nesting vectors, in good comparison with density-functional theory calculations, and (iii) the existence of hot-spot lines a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
99
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 79 publications
(115 citation statements)
references
References 48 publications
15
99
1
Order By: Relevance
“…This smallness of the lattice change implies that the hidden-order transition is driven by an electronic ordering, and small but finite electron-lattice coupling gives rise to the lattice distortion. It should be noted that in ironpnictides the large orthorhombicity is believed to be associated with the 'ferroic' (Q ¼ 0) orbital ordering, which is in sharp contrast to the URu 2 Si 2 case where the hidden order is most likely an antiferroic order with the wave vector Q ¼ (001) 6,7,[9][10][11][12] . Such an antiferroic ordering is expected to couple only weakly to the ferroic Q ¼ 0 orthorhombic distortion especially for high-rank multipole orders, in which the degree of local electronic distributions near the atoms are much smaller than that of dipoles in the antiferromagnetic case.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…This smallness of the lattice change implies that the hidden-order transition is driven by an electronic ordering, and small but finite electron-lattice coupling gives rise to the lattice distortion. It should be noted that in ironpnictides the large orthorhombicity is believed to be associated with the 'ferroic' (Q ¼ 0) orbital ordering, which is in sharp contrast to the URu 2 Si 2 case where the hidden order is most likely an antiferroic order with the wave vector Q ¼ (001) 6,7,[9][10][11][12] . Such an antiferroic ordering is expected to couple only weakly to the ferroic Q ¼ 0 orthorhombic distortion especially for high-rank multipole orders, in which the degree of local electronic distributions near the atoms are much smaller than that of dipoles in the antiferromagnetic case.…”
Section: Discussionmentioning
confidence: 92%
“…139 in the international tables for crystallography), which has 15 maximal non-isomorphic subgroups. Recent quantum oscillations 9 and angle-resolved photoemission spectroscopy [10][11][12] studies have revealed that the electronic structure in the hidden-order phase is similar to that of antiferromagneitc phase under pressure. This implies that in the hidden-order phase the Brillouin Zone is folded with the antiferroic wave vector Q ¼ (001) and the nested parts of Fermi surface are gapped as in the antiferromagnetic phase 13 .…”
mentioning
confidence: 99%
“…Measurements of high purity specimens have also driven investigations of the Fermi surface which, surprisingly, shows little change as the ground state is driven from hidden order to antiferromagnetism as a function of pressure [6,[20][21][22]. High quality specimens have also been essential for sensitive measurements such as STM [23,24] and ARPES [25]. In fact, the influence of sample purity is even reflected in bulk measurements such as electrical resistivity, where T c , T 0 and the power law dependence of ρ(T ) at low temperatures are all related to RRR [17].…”
Section: Introductionmentioning
confidence: 99%
“…In presenting the results, we focus on the representative electronic properties obtained from ARPES, 30,32,33 and the spin-excitation spectrum measured by inelastic neutron scattering (INS) experiment. 3,4 Figure 3 gives the single-particle maps along several representative momentum cuts, and the FS topology before and after the HO transition.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, the electronic structure of this actinide compound can be described adequately by first-principles calculation, without invoking Kondo-like physics. In fact, both DFT calculation 9 and angle-resolved photoemission spectroscopy (ARPES) measurement 30 have ruled out the presence of d electrons within the ±500 meV vicinity of the Fermi level to cause any significant hybridizations. Of course, among the octet and sextet multiplets of 5f electrons, variable renormalizations to different states can cause mixing between localized and itinerant electrons within the f states.…”
Section: Computations Detailsmentioning
confidence: 99%